2014
DOI: 10.1002/mop.28324
|View full text |Cite
|
Sign up to set email alerts
|

Design of a high‐gain ultra‐wideband slot antenna using frequency selective surface

Abstract: A CPW‐feed prototype slot antenna for ultra‐wideband applications is proposed. The slot is made by etching on the ground plane, the union of two elliptical structures placed at right angles. The fractal shape antenna is excited by two stepped CPW feed. To enhance the gain, a compact ultra‐wideband frequency selective surface (FSS) structure is designed and implemented. The measured impedance bandwidth of antenna with and without FSS is nearly same and equal to 9.0 GHz from 3.6 to 12.6 GHz. The measured peak ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…A frequency selective surface (FSS) method with a dual-layer reflector is used which helps in the gain enhancement and impedance matching. The distance between the antenna and reflector can be approximated by (11) Another high gain antenna with FSS has been designed by etching two elliptical structures for the slot [45]. The gain of the antenna without the FSS is very low and has been further enhanced with the presence of FSS.…”
Section: E Tapered Slot Antennamentioning
confidence: 99%
See 1 more Smart Citation
“…A frequency selective surface (FSS) method with a dual-layer reflector is used which helps in the gain enhancement and impedance matching. The distance between the antenna and reflector can be approximated by (11) Another high gain antenna with FSS has been designed by etching two elliptical structures for the slot [45]. The gain of the antenna without the FSS is very low and has been further enhanced with the presence of FSS.…”
Section: E Tapered Slot Antennamentioning
confidence: 99%
“…Tables 5 and 6 shows the results obtained from a tapered slotted antennas, dipole, spiral and cone antennas. From the results shown in Table 5, it can be observed that the tapered slot antenna (TSA) designed in [12], double exponentially tapered slot antenna (DETSA) designed in [13] and eye-shaped slotted antenna designed in [45] have comparatively high gain with greater percentage of bandwidth. The good performance of tapered slot antennas is mainly due to the coplanar properties of radiator and ground, and tapering characteristics, which is helpful in order to improve the performance of the antennas.…”
Section: F Dipole Cone and Spiral Antennamentioning
confidence: 99%
“…UWB patch monopole antennas have been utilized for many MWI applications . UDR, high gain, and extensive bandwidth of UWB antenna are required in designing MWI baggage scanner system.…”
Section: Introductionmentioning
confidence: 99%
“…In recent literature, several multi‐layer as well as single‐layer FSS designs for UWB applications are presented . A two‐layer FSS with unit cell consisting of a modified cross‐loop is presented in ref.…”
Section: Introductionmentioning
confidence: 99%
“…In ref. , a very large percentage bandwidth of 102% (3.9–11.10 GHz) with a single‐layer FSS is achieved; however, the lower frequency response is very poor not covering the critical part of UWB from 3.1 to 3.9 GHz. In ref.…”
Section: Introductionmentioning
confidence: 99%